An Afro-Communitarian Compatibilist View on Rights?. Issue 159 (1st July 2019) - Kumalo, Siseko H.
Abstract : The historical debate, in African philosophy, on personhood has been characterised by radical and moderate communitarianism seen through the scholarship of Menkiti (1984) and Gyekye (1997) and continues contemporarily with scholars considering its implications on contemporary conceptions of rights. Responding to Chemhuru's compatibilist view that, he maintains, safeguards and guarantees individual rights, I showcase how his conception of the community as prior to the individual betrays his project. Using the African Charter on Human and Peoples Rights to contextualise rights discourse in Afro-communitarianism, Chemhuru avers that once collective rights have been gained, individuals can claim their rights. I critique this position to suggest that Chemhuru undermines his own project of compatibilism through placing the community prior to the individual. Using the Civil Union Act (2006) as a legislative framework that safeguards and guarantees individual human rights, I test Chemhuru's compatibilist view. I conclude by highlighting the divergences between constitutionalism and Afro-communitarianism.